Impedance spectroscopy advanced applications : battery research, bioimpedance, system design - Kanoun, Olfa (Walter de Gruyter, 2018)
Impedance Spectroscopy is a powerful measurement method used in many application fields such as electrochemistry, material science, biology and medicine, semiconductor industry and sensors. Using the complex impedance at various frequencies increases the informational basis that can be gained during a measurement. It helps to separate different effects that contribute to a measurement and, together with advanced mathematical methods, non-accessible quantities can be calculated. This book covers new advances in the field of impedance spectroscopy including fundamentals, methods and applications. It releases scientific contributions from the International Workshop on Impedance Spectroscopy (IWIS) as extended chapters including detailed information about recent scientific research results. The book includes typically subsections on: Fundamental of Impedance Spectroscopy Bio impedance Techniques and Applications Impedance Spectroscopy for Energy Storage Systems Sensors Based on Impedance Spectroscopy Measurement systems Excitation Signals Modeling Parameter extraction
Keywords: Engineering measurement & calibration; Materials; Technology & Engineering / Automation; Impedance spectroscopy -- Industrial applications; Materials -- Testing; Impedanzspektroskopie; Electronic books; Aufsatzsammlung